Analisis produktivitas pariwisata: Studi kasus pada beberapa negara berdasarkan perbedaan karakter wilayah - Andaru Rachmaning Dias Prayitno; Arif Purwantoro; Nurareni Widi Astuti; Tri Haryanto (Universitas Negeri Surabaya, 2023)
Tourism productivity has a role in driving economic growth, creating jobs, increasing people's income, and building tourism infrastructure. Measurement of tourism productivity is important because it provides the information needed to measure the performance of the tourism sector, plan sustainable development, identify growth opportunities and make smart investment decisions. The type of approach used is a descriptive qualitative approach, namely an approach that uses more systematic analysis based on assumptions and critical thinking. This approach is used to answer the research objective, namely to determine tourism productivity in a country. The type of data used is secondary data obtained from several relevant and valid scientific journals regarding tourism productivity that have been published previously. Not only scientific journals, this research also uses government publication data. The results of the research discussion aim to make readers understand and know tourism productivity in several countries and provide relevant information for decision makers in local governments and the tourism industry.